1999
DOI: 10.1177/088307389901400607
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Free Radical Scavenging Enzyme Activity in Children

Abstract: Oxygen-derived free radicals play an important role in multiple pediatric neurologic diseases. Five intracellular free radical scavenging enzymes and three trace elements provide a significant portion of the body's defenses against free radical-mediated injury. Although the effects of age, sex, and ethnicity on the body's antioxidant defenses have been described, no study has examined whether racial differences exist. This pilot study sought to determine the effect of racial differences on the activity of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…All infants with MM had deficiencies in erythrocyte FRSE activities. The differences identified in FRSE activities were consistent with the results indicated in the literature (6,7,10,12). Graff et al (7) found that there were significant differences between patient and control groups.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…All infants with MM had deficiencies in erythrocyte FRSE activities. The differences identified in FRSE activities were consistent with the results indicated in the literature (6,7,10,12). Graff et al (7) found that there were significant differences between patient and control groups.…”
Section: Discussionsupporting
confidence: 89%
“…Only a few articles describing abnormal FRSE activities in infants with MM have been published (6,7,8,10). Previous studies measured FRSE activities, especially GSH-related reported a similar observation.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…To the authors' knowledge there is little published information about socio-economic determinants of Se status. Likewise, apart from recent evidence of higher plasma Se concentration and RBC GPx activity in a small number of AfricanAmerican children compared with their Caucasian counterparts (Glauser et al, 1999), ethnic differences in Se status indices appear not to have been reported elsewhere (Alfthan & Nève, 1996). It seems unlikely that the non-Caucasians, Selenium status in young people CJ Bates et al who had higher plasma and RBC Se concentrations (Table 7), also had higher Se intake than the Caucasians.…”
Section: Discussionmentioning
confidence: 88%